1998
DOI: 10.1177/0093854898025002005
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Adult Criminal Status from Juvenile Psychological Assessment

Abstract: A total of 121 juvenile offenders assigned to a regional assessment center in Medicine Hat, Alberta, Canada, for comprehensive psychological assessment between 1979 and 1984 were administered a test battery that included the WISC-R, the MMPI, and the Rorschach test. The offenders included 84 males and 37 females ages 12 to 15; among them were 48 Native Americans. In 1992, after a mean elapsed time of 9.9 years, all 121 were followed up and classified as either guilty ( n = 61) or not guilty ( n = 60) of a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

1999
1999
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…It is plausible that the future of a specialized court for adolescents hinges on demonstration of the efficacy of programs in youth services systems to reduce criminal recidivism. Although there have been studies of criminal recidivism during adolescence and adulthood, there is a paucity of studies about the criminal recidivism of adolescents during adulthood, especially studies that examine dynamic risk factors such as those on the Jesness Inventory or Carlson Psychological Survey (e.g., Anderson & Walsh, 1998;Ashford & LeCroy, 1990;Benda, 1989;Brown, Miller, & Jenkins, 1989;Lewis, 1989;Lie, 1988). The primary focus of this study is these dynamic risk factors because they are amenable to intervention to reduce recidivism.…”
mentioning
confidence: 99%
“…It is plausible that the future of a specialized court for adolescents hinges on demonstration of the efficacy of programs in youth services systems to reduce criminal recidivism. Although there have been studies of criminal recidivism during adolescence and adulthood, there is a paucity of studies about the criminal recidivism of adolescents during adulthood, especially studies that examine dynamic risk factors such as those on the Jesness Inventory or Carlson Psychological Survey (e.g., Anderson & Walsh, 1998;Ashford & LeCroy, 1990;Benda, 1989;Brown, Miller, & Jenkins, 1989;Lewis, 1989;Lie, 1988). The primary focus of this study is these dynamic risk factors because they are amenable to intervention to reduce recidivism.…”
mentioning
confidence: 99%
“…De acuerdo con la literatura, la dirección de la relación entre conducta escolar y antisocial no ha sido aclarada. Sin embargo, se ha encontrado consistentemente que los jóvenes que delinquen presentan problemas escolares (Anderson y Walsh, 1998).…”
Section: Discussionunclassified
“…Las secuelas podrían manifestarse también en el bajo aprovechamiento escolar o en conductas problemáticas de los menores. Por ejemplo, en un estudio llevado a cabo por Anderson y Walsh (1998) se encontró que jóvenes con baja eficiencia verbal provenían de hogares con bajas oportunidades de mejorar su capacidad lingüística y mostraron más conducta antisocial y delictiva cuando fueron adolescentes y adultos. Es probable que este efecto se deba a que la familia no sea capaz de dotar a los menores de las capacidades necesarias de interacción prosocial (conseguir un buen empleo, interactuar de manera positiva con otras personas) y esto los lleve a conseguir sus satisfactores de manera antisocial o delictiva (Hunter, comunicación personal, 5 de julio de 2000).…”
unclassified
“…Instruments that sample logically relevant domains (e.g., Abel & Becker Cognitive Distortions Scale, Attitudes Towards Women, Burt Rape Myth;Salter, 1988) are frequently open to social desirability in¯uences and often uninformative of anything except that oenders are also aware of social norms (e.g., Langevin et al, 1979). There is evidence that projective tests are predictive of general recidivism for juvenile oenders (Anderson & Walsh, 1998), and recent data have suggested that the Rorschach is less vulnerable to response bias (e.g., minimization and malingering) than objective measures such as the MMPI (Wasyliw, Benn, Ganellen, Wasyliw, Haywood, & Grossman, 1996). However, projective tests are costly to administer, score, and interpret; and there have been questions regarding the validity and reliability of the Rorschach (Wood, Nezworski, & Stejskal, 1996).…”
Section: Who Are Sex Offenders?mentioning
confidence: 99%